2008
DOI: 10.1097/wnr.0b013e3283060ab6
|View full text |Cite
|
Sign up to set email alerts
|

MAO A VNTR polymorphism and variation in human morphology: a VBM study

Abstract: The X-linked monoamine oxidase A (MAO A) gene, coding for an enzyme especially involved in the serotonin catabolism, presents a well-characterized functional polymorphism (long and short variants) in the promoter region that alters the transcriptional activity of the gene and hence the function of the corresponding proteins. Using optimized voxel-based morphometry, we studied the effect of this functional polymorphism on brain morphology in normal individuals. Fifty-nine male healthy individuals (33 MAO A-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
(38 reference statements)
0
20
1
Order By: Relevance
“…Different results might depend upon the different MRI volumetric approach employed by Meyer-Lindenberg et al (2006) (VBM), although in an our previous VBM study using an underpowered sample we did not detect significant association between MAO A and amygdala concentration (Cerasa et al, 2008b). Generally, VBM and volumetric studies often are not directly comparable.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Different results might depend upon the different MRI volumetric approach employed by Meyer-Lindenberg et al (2006) (VBM), although in an our previous VBM study using an underpowered sample we did not detect significant association between MAO A and amygdala concentration (Cerasa et al, 2008b). Generally, VBM and volumetric studies often are not directly comparable.…”
Section: Discussionmentioning
confidence: 80%
“…Although there is consistent evidence that the MAO A polymorphism impacts limbic function, possible morphological changes underlying such a functional polymorphism remain to be clarified. In fact, there are few morphological studies that, using voxel-based morphometry (VBM), indirectly investigated the association of this genotype with amygdala volume, and these studies produced contrasting findings (Meyer-Lindenberg et al, 2006;Cerasa et al, 2008b). VBM is a morphological technique that performs a statistical mapping of differences in brain morphology voxel-byvoxel, which produces grey matter "density" or "concentration" measures, or volume differences between two groups, respectively; however, these are relative measures and not absolute volumes (Eckert et al, 2006;Makris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of phenotypical features observed in MAO-A Neo mice is strikingly similar to the neuropsychological and morphological correlates of low-activity allelic MAO-A variants in humans, including structural abnormalities in the orbitofrontal cortex, social deficits, maladaptive threat perception, and lack of inherent aggressiveness (at least in the absence of concurring environmental factors) (Caspi et al, 2002;Cerasa et al, 2010;Cerasa et al, 2008;Kim-Cohen et al, 2006;Lee and Ham, 2008;MeyerLindenberg et al, 2006;Williams et al, 2009). These crossspecies analogies highlight the translational validity of MAO-A Neo mice as a dependable murine model to investigate the neurobiological bases of the subtle aberrances associated with low MAO-A activity, as well as their implication in the vulnerability to pathological aggression and related psychiatric disorders.…”
Section: Discussionmentioning
confidence: 88%
“…In particular, several studies have shown that male individuals with the 3R haplotype exhibit morphological alterations of the orbitofrontal cortex (Meyer-Lindenberg et al , 2006; Cerasa et al , 2008, 2010), as well as functional abnormalities in several cortical and limbic regions, including prefrontal cortex, amygdala, and hippocampus (Meyer-Lindenberg et al , 2006; Passamonti et al , 2006). …”
Section: Phenotypical Outcomes Of Mao-a Deficitmentioning
confidence: 99%